POPULATION STATUS AND DISTRIBUTION OF RHESUS MACAQUE Macaca mulatta (Zimmermann, 1780) AT CAT BA NATIONAL PARK, VIETNAM - Van Dung, Tran; Ngoc Khoi, Nguyen; Huy Cam, Nguyen; Thi Ha, Nguyen; Viet Dai, Phan; Van Luong, Nong; Van Tay, Nguyen; Van Thong, Phan; Tien Thinh, Vu (Journal of Forestry Science and Technology, 2019)
There is little information known about the Rhesus macaque (Macaca mulatta) distribution and population status within Vietnam. Information regarding species distribution and population status is crucial for effectively planning, and designing a conservation strategy. Thus, this study aimed to acquire data and information about M. mulatta status and distribution at Cat Ba National Park, Hai Phong, Vietnam. Survey interviews and line transect surveys have been applied to detect populations and the distribution of the species. Four marine transects and two terrestrial transects were surveyed from June to August 2018. The study results showed that there were 222 individuals and 11 groups of Rhesus macaque observed in Cat Ba National Park. The average number of individuals in each group is 20. In transect number 2 (Van Ta – Hang Cai), the surveyors observed the highest number of monkeys among all transects with 108 individuals in 6 groups. The average occurrence frequency is 0.11 group/km and 2.31 individuals/km. For the distribution characteristics, the M. mulatta mainly distributed in the east of the National Park such as the Cua Dong, Gio Cung, and Van Ta areas. However, the study did not detect the species in the north and southwest of Cat Ba Island. The study also showed that the suitable elevation of M. mulatta ranges from 0 to 150 m a.s.l. The main habitats for the species in Cat Ba national park are evergreen forests, and shrubs on limestone mountains and grassland.